E‐learning cultural competence for public health workers: A feasibility and pilot study. Issue 5 (21st May 2021) - Chae, Duckhee; Kim, Yunekyong; Ryu, Jeeheon; Asami, Keiko; Kim, Jaseon; Kim, Kukhyeon
Abstract: Objective: To describe the development, feasibility, and preliminary efficacy of a seven‐module e‐learning for enhancing cultural competence of public health workers. Design: The study was based on the framework of the new Medical Research Council; a mixed methods design was used. Sample: A four‐week pilot cluster‐randomized controlled trial was conducted with 39 public health workers and 74 migrants in South Korea. Feasibility and preliminary efficacy were assessed according to initiation, retention, adherence, usability, acceptability, individual and organizational cultural competence, and migrant trust and satisfaction. Quantitative data were collected at baseline, 4 weeks, and 12 weeks. Focus group interviews were conducted with eight public health workers at 12 weeks. Results: Initiation, retention, and adherence rates were high. Participants agreed on acceptability, but exhibited mixed results on usability. Participants were satisfied with "well‐structured content, " "authentic case stories and videos, " "increased interest in migrant care, " and "opportunity for self‐reflection." However, "flawless and trouble‐free system, " "screen design for easy navigation, " "instructor's expertise, " and "more situational cases and videos" were desired. Statistically significant differences were observed for individual cultural competence, migrant trust, and satisfaction. Conclusion: Generally, the intervention seems feasible and has preliminary efficacy, yet usability improvement is necessary for full‐scale randomized controlled trials.